Anti-programmed cell death-1 (PD-1) monoclonal antibodies involve reversible cranial dura matter. Issue 9 (13th September 2021) - Kataoka, Hiroshi; Shimada, Daisuke; Nanaura, Hitoki; Sugie, Kazuma
ABSTRACT: This case is the first document to describe a patient receiving anti-programmed cell death 1 (PD-1) antibodies which showed cranial dura matter involvement. According to the increasing use of anti-PD-1 monoclonal antibodies, adverse effects can occur in several organs since its ligand PD-L1 and PD-L2 are expressed in a wide variety of tissues. The estimated rate of neurological complications is 1–4.2% of patients, and neuromuscular disorders are the most common. Adverse effects on the central nervous system including encephalitis are less frequent. Here, a patient receiving anti-PD-1 antibodies showed cranial dura matter involvement, and the dura enhancement on MRI was resolved by withdrawal of the treatment with anti-PD-1 antibodies only.